The microbiota‐gut‐brain axis and epilepsy from a multidisciplinary perspective: Clinical evidence and technological solutions for improvement of in vitro preclinical models - Federica Fusco; Simone Perottoni; Carmen Giordano; Antonella Riva; Luigi Francesco Iannone; Carmen De Caro; Emilio Russo; Diego Albani; Pasquale Striano (Wiley, 2022)
Abstract Epilepsy is a common neurological disease characterized by the enduring predisposition of the brain to generate seizures. Among the recognized causes, a role played by the gut microbiota in epilepsy has been hypothesized and supported by new investigative approaches. To dissect the microbiota‐gut‐brain (MGB) axis involvement in epilepsy, in vitro modeling approaches arouse interest among researchers in the field. This review summarizes, first of all, the evidence of a role of the MGB axis in epilepsy by providing an overview of the recent clinical and preclinical studies and showing how dietary modification, microbiome supplementations, and hence, microbiota alterations may have an impact on seizures. Subsequently, the currently available strategies to study epilepsy on animal and in vitro models are described, focusing attention on these latter and the technological challenges for integration with already existing MGB axis models. Finally, the implementation of existing epilepsy in vitro systems is discussed, offering a complete overview of the available technological tools which may improve reliability and clinical translation of the results towards the development of innovative therapeutic approaches, taking advantage of complementary technologies.